FINANCIAL REPORTING IN THE FEDERAL GOVERNMENT. - Morey, Lloyd (The Accounting Review, 1942)
The United States government is the largest, the most extensive, and the most diversified business enterprise in the world. Its financial operations involve practically every kind and type of situation found in private business and in other forms of government, and many conditions not elsewhere found. Hence no simple or direct statements of the problem or of its solution are possible. Yet the purposes of financial reporting in the Federal government are the same as in any other government or in any private enterprise in which the public is materially concerned. They are to compile and disseminate information concerning financial operations and condition, for the benefit and guidance of management, investors, and the public. To these ends, each phase of the accounting and reporting should be directed. To be of the most service, the reports should be based on uniform standards and terminology consistently followed, should be comprehensive and truly informative, and should be rendered promptly and regularly.